Orientasi Nilai Budaya Petani Tembakau di Dataran Tinggi Gayo - Iromi Ilham; Abdullah Akhyar Nasution; Amiruddin Ketaren; Marliza Marliza; Jamilah Jamilah; M Fathi (FISIP Universitas Malikussaleh, 2022)
The rise of noble tobacco farming is seen again today in the Gayo Highlands after it was once glorious in the 1980s. There were many things that reference ideas, motivations, values, and orientations behind them. This study analyzed the cultural value orientation of tobacco farmers in Gayo so that it continues to carry out planting practices to this day. Furthermore, this study also explored the various habits tobacco farmers have in developing tobacco, including the inheritance pattern of tobacco planting culture between generations. The research, which took the locus in Central Aceh, used a qualitative approach by referring to C. Kluckhohn's concept of